SUMOylation and deimination of proteins: two epigenetic modifications involved in Giardia encystation - Vranych, Cecilia Verónica (2014)
SUMOylation, a post-translational modification of proteins, has been recently described as vital in eukaryotic cells. In a previous work, we analyzed the role of SUMO protein and the genes encoding the putative enzymes of the SUMOylation pathway in the parasite Giardia lamblia. Although we observed several SUMOylated proteins, only the enzyme Arginine Deiminase (ADI) was confirmed as a SUMOylated substrate. ADI is involved in the survival of the parasite and, besides its role in ATP production, it also catalyzes the modification of arginine residues to citrulline in the cytoplasmic tail of surface proteins. During encystation, however, ADI translocates to the nuclei and downregulates the expression of the Cyst Wall Protein 2 (CWP2). In this work, we made site-specific mutation of the ADI SUMOylation site (Lys101) and observed that transgenic trophozoites did not translocate to the nuclei at the first steps of encystation but shuttled in the nuclei late during this process through classic nuclear localization signals. Inside the nuclei, ADI acts as a peptidyl arginine deiminase, being probably involved in the downregulation of CWPs expression and cyst wall formation. Our results strongly indicate that ADI plays a regulatory role during encystation in which post-translational modifications of proteins are key players.